Bad prospects for the detection of giant stars' tidal disruption: effect of the ambient medium on bound debris. Issue 3 (2nd March 2016) - Bonnerot, Clément; Rossi, Elena M.; Lodato, Giuseppe
Abstract : Most massive galaxies are thought to contain a supermassive black hole in their centre surrounded by a tenuous gas environment, leading to no significant emission. In these quiescent galaxies, tidal disruption events represent a powerful detection method for the central black hole. Following the disruption, the stellar debris evolves into an elongated gas stream, which partly falls back towards the disruption site and accretes on to the black hole producing a luminous flare. Using an analytical treatment, we investigate the interaction between the debris stream and the gas environment of quiescent galaxies. Although we find dynamical effects to be negligible, we demonstrate that Kelvin–Helmholtz instability can lead to the dissolution of the stream into the ambient medium before it reaches the black hole, likely dimming the associated flare. This result is robust against the presence of a typical stellar magnetic field and fast cooling within the stream. Furthermore, we find this effect to be enhanced for disruptions involving more massive black holes and/or giant stars. Consequently, although disruptions of evolved stars have been proposed as a useful probe of black holes with masses ≳ 10 8  M⊙, we argue that the associated flares are likely less luminous than expected.